What’s new in the treatment of atopic dermatitis? - Nowicki, Roman (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Atopic dermatitis (AD, atopic eczema) is one of the most common inflammatory skin diseases, with a chronic or relapsing course and strong itching. The prevalence of AD has increased over the last years tremendously. Atopic dermatitis impacts negatively the quality of life of both patients and their families. Largely on the basis of the recently described association of atopic dermatitis and the genetically inherited abnormalities in filaggrin expression, atopic dermatitis is considered at least partially a primary disorder of stratum corneum structure and function. Treatments improving this function may reduce the likelihood of further aggravation of the disease. The use of proper emollients continues to be the main therapeutic approach to this problem. Emollients have the potential to reduce pruritus, xerosis, and infection rates by restoring integrity to the damaged barrier. The two primary classes of drugs used to treat AD are topical corticosteroids (TCs) and topical calcineurin inhibitors (TCIs). Topical therapies are the mainstay in the treatment of AD, and are effective in the majority of patients with mild and localized disease. In patients with widespread or recalcitrant severe dermatitis, systemic therapies may be required. Frequently used systemic therapies are immunosuppressants, immune response modifiers, antiinflammatories, antihistamines, and antibiotics. Education of patients and caregivers about benefits and limitations of different therapeutic methods, about adverse events, and information how to use medical therapies appropriately are an important part of treatment of AD. General dermatologists play a pivotal role in the management of this chronic condition.